Pengaruh Audit Operasional, Pengendalian Internal, Dan Good Clinical Governance Terhadap Efektivitas Pelayanan Kesehatan Pasien Bpjs Di Rumah Sakit - Winda Riyasari; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to prove that the effect of operational audits, good internal and clinical governance in hospitals has an effect on the health services of goverment of public health patients in hospitals. The sample selection in this research used purposive sampling method with various criteria according to the research objectives. The total sample used as the object of research in this study is the desire of 15 hospitals in Padang city with the category of government-owned or private hospitals. The data analysis technique used in this study was a questionnaire that was designed according to the variables used in this study. The results of this study can prove that the audit has a positive effect on the health of goverment of public health patients in the hospital. With the results of the sig value 0.001 <0.05, and the t-count value of 3.366> t-t table 1.992, it can be concluded that the hypothesis H1 is accepted. In addition, this study can also prove empirically that good clinical governance has a positive effect on the health of goverment of public health patients in the hospital with a sig value of 0.002 <0.05 with a value of t-count 3.162> t-t table 1.992. So it can be concluded that the hypothesis H3 is accepted, while the internal control variable has no effect on the influence of goverment of public health patient health services in the hospital. it can be concluded that the hypothesis H2 is rejected. Suggestions for further research are expected to increase the number of research samples and also the year of observation. Can also use other variables that are used to measure the effectiveness of BPJS patient health services in the hospital.